(untitled) (European Journal of Health Research, 2019)
The literature indicates that the family’s beliefs of illness influence in patient’s beliefs, determine the reaction and attitude that family members have towards him, and influences the coping strategies he uses, as well as his evolution . The aim of this study was to describe the beliefs that both patients with ED and their relatives have of the disease, and to analyze how the degree of congruence between them is related to the psychosocial adjustment and psychological distress of these patients. 98 women diagnosed with an eating disorder and 60 family members participated. The Revised Illness Perception Questionnaire (IPQ-R), the Hospital Anxiety and Depression Scale (HADS) and the Psychosocial Adaptation Questionnaire (PAIS) were administered. When patients and relatives considered that the illness was distressing, chronic and with a high identity, these patients showed greater emotional distress than patients who did not agree with their relatives in these dimensions. When patients and family members considered that the disease had strong negative consequences, these patients reported lower levels of educational adjustment and more sexual problems. However, when patients and family members had positive beliefs about disease control, these patients showed lower levels of depression and anxiety than patients who did not agree with their family members.